EFFECTS OF GINGER (Zingiber officinale) and CLOVE (Syzygium aromaticum) EXTRACTS ON THE QUALITY OF Clarias gariepinus PROCESSED WITH KAINJI MODIFIED DRUM KILN - Kefas, M.; Kolapo, A.; Jauro, I. A.; Haziel, H. (FUDMA JOURNAL OF SCIENCES, 2023)
The research was aimed to evaluate the preservative effects of Ginger and Clove extract on the quality and shelf-life of Clarias gariepinus processed with Kainji Modified Drum Kiln. Thirty six (36) Clarias gariepinus species were obtained from Kabod Fish Farm, Jimeta-Yola. Phytochemical compositions of ginger and clove extract indicated the presence of Saponins, Flavonoids and Tannins in both Ginger and Clove, while Glycosides, Steroids and Trepenoids were only detected in Cloves. The Catfish samples were immersed in the aqueous solution prepared (Ginger Aqueous Solution (GAS) and Clove Aqueous Solution (CAS)) separately and transferred to the Kiln for smoking. Data were analyzed using ANOVA. There was no significant difference (P>0.05) in all the fish samples treated with ginger, clove and combine (ginger and clove). The proximate composition of freshly processed and preserved C. gariepinus showed low crude protein (36.31 – 42.47 g/100g Dry matter) and crude lipid (16.65 – 24.35g/100g Dry matter) while crude protein (50.80– 56.87 g/100g Dry matter) and crude lipid decreases (14.98 – 19.00 g/100g Dry matter). The results show that the Catfish samples treated with ginger, clove and combined (ginger and clove) as preservatives prior to processing indicates the effectiveness of these preservatives in controlling yeast and mold growth and capable of inhibiting microbial growth in stored Catfish products that was processed by Kiln. The improvement and development of packaging (using low cost local packaging materials) and good storage conditions will protect the products against spoilage and breakages for more than twelve (12) weeks without any insect